Physicochemical Effects of Niobic Acid Addition Into Dental Adhesives - Garcia, Isadora Martini; Leitune, Vicente Castelo Branco; Balbinot, Gabrielade Souza; Balhaddad, AbdulRahman A.; Melo, Mary Anne S.; Samuel, Susana Maria Werner; Collares, Fabrício Mezzomo (Frontiers in Materials, 2021)
The aim of this study was to evaluate the incorporation of niobic acid into experimental dental adhesives, and compare these adhesives to niobium pentoxide containing adhesives. A control group without Nb2O5·nH2O or Nb2O5 was also used for comparison. Niobium-based particles have been used as a feasible approach, mainly because of their bioactivity. In this study, hydrated niobium pentoxide, also called niobic acid (Nb2O5·nH2O), was incorporated into an experimental dental adhesive as a potential catalyst for monomer conversion. A base resin for dental adhesive was formulated with methacrylate monomers and photoinitiators. Two types of oxides were tested as filler for this adhesive: Nb2O5·nH2O or niobium pentoxide (Nb2O5). Both fillers were added separately into the experimental adhesive at 0, 2.5, 5, and 10 wt.%. One group without Nb2O5·nH2O or Nb2O5 (0 wt.% of filler addition) was used as a control group. The formulated materials were analyzed for radiopacity according to the ISO 4049 and used FTIR analysis to assess the degree of conversion (DC) and the maximum polymerization rate (RPmax). Mechanical properties were analyzed by ultimate tensile strength (UTS) in a testing machine. Softening in solvent was conducted by measuring Knoop microhardness before and after immersion of samples in ethanol. Normality of data was assessed with Shapiro-Wilk, and comparisons between factors were conducted with two-way ANOVA and Tukey at 5 % of significance. Both fillers, Nb2O5 or Nb2O5·nH2O, increased the radiopacity of dental adhesives in comparison to the unfilled adhesive (p<0.05). There were no differences among groups for the UTS (p>0.05), and all groups containing Nb2O5 or Nb2O5·nH2O improved the resistance against softening in solvent (p<0.05). The groups with 5 and 10 wt.% addition of Nb2O5 showed decreased DC compared to the control group (p<0.05), while the addition of Nb2O5·nH2O up to 10 wt.% did not alter the DC (p>0.05). The polymerization rate did not change among groups (p>0.05). In conclusion, Nb2O5·nH2O is a promising filler to be incorporated into dental adhesives providing proper mechanical properties, improved resistance against solvents, and increased radiopacity, without changing the DC.